A computational protocol for the study of circularly polarized phosphorescence and circular dichroism in spin-forbidden absorption. Issue 29 (7th August 2015) - Kamiński, Maciej; Cukras, Janusz; Pecul, Magdalena; Rizzo, Antonio; Coriani, Sonia
<x xml:space="preserve">Abstract</x> First computational approach for circularly polarized phosphorescence.